Pelatihan Penyusunan Modul Ajar Berdiferensiasi bagi Forum MGMP Bahasa Indonesia Kabupaten Kampar - Mukhlis, Muhammad; Yuliawan, Tri; Piliang, Wilda Srihastuty Handayani; Sukenti, Desi; Shafina, Vira; Arni Natalina Br Siburian, Desi (UIR Press, 2025)
Community Service Program aims to enhance the competence of Indonesian language teachers in designing differentiated teaching modules in Kampar Regency. The training employed a participatory approach through discussions, hands-on practice, and the use of technology in module development. Evaluation results indicate that 99% of participants were satisfied with the program, and their understanding of differentiated learning improved. The aspect of diverse information sources received the highest score, while variation in instruction and alternative assignments still need improvement. This program also promotes sustainability through mentoring and collaboration with MGMP. With these positive outcomes, it is expected that teachers will continue developing innovative and adaptive teaching modules to improve the quality of Indonesian language learning.